Environment protection in developing countries - Heptulla, Najma, editor (New Delhi : Oxford & IBH Pub. Co., 1993)
Selected contributed papers of a seminar.
"Seminar on Environmental Protection and Developing Countries, Tuesday the 12th May, 1992"--P. [328].
Includes bibliographical references.
Keywords: Environmental protection -- Developing countries; Environmental policy -- Developing countries; Human ecology -- Developing countries